2020
DOI: 10.1016/j.celrep.2019.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 3q26 Gain Is an Early Event Driving Coordinated Overexpression of the PRKCI, SOX2, and ECT2 Oncogenes in Lung Squamous Cell Carcinoma

Abstract: Highlights d 3q26 CNG and TP53 mutation associate with progression of carcinoma in situ to LSCC d PRKCI, SOX2, and ECT2 overexpression transforms Trp53 À/À mouse lung basal stem cells d Active PKCi-SOX2 and PKCi-ECT2 signaling is required for LBSC transformation d A PKCi-SOX2 molecular signature suggests unique therapeutic vulnerabilities in LSCC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…Our published studies have demonstrated that PKC phosphorylates other targets within the nucleus to promote the transformed phenotype of cancer cells. Specifically, PKC phosphorylates the oncogenic transcription factors SOX2 and ELF3 in LSCC and LADC cells, respectively, leading to activation of transcriptional activity (52)(53)(54)(55). Indeed, our recent study demonstrated that PKC-mediated SOX2 phosphorylation is required for expression of a SOX2 transcriptional program that drives lineage-restricted transformation of lung basal stem cells, a major cell of origin, into LSCC (55).…”
Section: Phosphorylation-regulated Ubf1-ect2 Binding On Ribosomal Dnamentioning
confidence: 87%
“…Our published studies have demonstrated that PKC phosphorylates other targets within the nucleus to promote the transformed phenotype of cancer cells. Specifically, PKC phosphorylates the oncogenic transcription factors SOX2 and ELF3 in LSCC and LADC cells, respectively, leading to activation of transcriptional activity (52)(53)(54)(55). Indeed, our recent study demonstrated that PKC-mediated SOX2 phosphorylation is required for expression of a SOX2 transcriptional program that drives lineage-restricted transformation of lung basal stem cells, a major cell of origin, into LSCC (55).…”
Section: Phosphorylation-regulated Ubf1-ect2 Binding On Ribosomal Dnamentioning
confidence: 87%
“…Targeted gene-sequencing analysis of both physiologically normal skin and normal esophageal epithelium revealed strong positive selection for canonical SCC driver mutations such as NOTCH1 , which exhibits mutation prevalence as high as 20% and 12 to 80% in normal skin and esophagus, respectively [ 119 , 120 ]. Furthermore, copy number gains (CNGs) critically linked with SCC development such as the amplification of chromosome 3q, which contains PIK3CA , TP63 , and SOX2 , were detected within normal esophageal tissue, and 3q26 CNG was recently reported to be an early event in LSCC development cooperating with mutant p53 to drive progression [ 121 ]. Ultimately, the mutational landscape of normal tissue demonstrates not only clonal expansion in the context of normal cells harboring mutations conferring a selective advantage but also more nuance and complexity in factors contributing to cancer initiation and intratumoral heterogeneity.…”
Section: Interplay Between Oncogenic Drivers and Metabolic Alteratmentioning
confidence: 99%
“…Inactivation of Trp53 (the mouse orthologue of TP53) in bulk mouse tracheal epithelial cells has been shown to enhance organoid formation efficiency 31 . When 3D cultures were initiated with purified basal cells, p53 deficiency increased both organoid number and size and enabled longer-term passaging, indicative of aberrant stem/progenitor cell self-renewal 32 . Depletion of Kelchlike ECH associated protein (KEAP1), a negative regulator of the oxidative stress response, also augmented organoid forming capacity of tracheal epithelial cells 31 .…”
Section: In Vitro Systemsmentioning
confidence: 99%
“…Using lentiviral vectors to model amplification of different genes located within the 3q26 chromosomal region, it has been shown that SOX2, ECT2 and PRKCI exert cooperative interactions to induce neoplastic transformation of Trp53-depleted murine basal cells 32 . In organoid cultures, SOX2, ECT2, and PRKCI were found to each have a dominant role in the control of basal cell self-renewal, cell proliferation and epithelial polarity, respectively.…”
Section: In Vitro Systemsmentioning
confidence: 99%
See 1 more Smart Citation